Love Island and Relationship Education - Porter, Janette; Standing, Kay (Frontiers in Sociology, 2020)
The rise of reality TV programmes focussing on relationships and the search for ‘love’ has focussed media attention on the portrayal of healthy relationships, gender roles and intimate partner abuse (IPVA). Love Island, a UK reality TV programme, was watched in 2019 by over 3 million viewers, a majority of whom are young women aged 16 to 34, though a younger teenage demographic also watch. Many of these younger viewers may be learning about what healthy relationships are like, and entering their first romantic relationships. Contestants behaviour on Love Island prompted Women’s Aid to issue a statement speaking out against unhealthy behaviours in relationships – especially “gaslighting”, a form of emotional abuse that makes someone question their own feelings, memories and version of reality. Based on our experience of running a relationship education program in 24 schools, as part of the Tender national partnership and our research with young people on their perceptions of Love Island, the paper will examine the role reality TV programmes; play in young people’s understandings of healthy relationships. It argues representations of relationships on Love Island are framed within normative heterosexuality and the normalisation of emotional abuse. However, we also argue that these programmes can be a catalyst for discussion amongst young people and open up spaces, especially online, to challenge dominant constructions of relationships. It also makes recommendations for education policy and practice around relationship and sex education in schools.